2021
DOI: 10.1002/cjce.24157
|View full text |Cite
|
Sign up to set email alerts
|

CeO2/TiO2/SiO2 nanocatalyst for the photocatalytic and sonophotocatalytic degradation of chlorpyrifos

Abstract: A new nanohybrid photocatalyst named cerium (IV) oxide (CeO 2 )/TiO 2 (titania)/silicon dioxide (SiO 2 ) was firstly synthesized employing the coprecipitation technique to elaborate the degradation efficiency of chlorpyrifos (CPS) as a relatively indelible organophosphorus pesticide in deionized water in photocatalytic and sonophotocatalytic processes. The influence of various parameters, including photocatalyst dosage, the CPS pesticide concentration, pH, and irradiation time, was investigated, and the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…All the synthetic approaches that have been identified are related to their own set of disadvantages, like long processing time, high temperature reaction, expensive and hard to scale up and complicated method. [28,30,[50][51][52] In the present study, we have synthesized graphene-CdS nanocomposites with a facile approach at low-temperatures and less reaction time, which is eco-friendly and cost-effective. Further exploration in an extensive literature review indicates that among all the reported literature, our catalyst has served as a better photocatalyst with lower catalyst dosage and less reaction time.…”
Section: Photocatalytic Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…All the synthetic approaches that have been identified are related to their own set of disadvantages, like long processing time, high temperature reaction, expensive and hard to scale up and complicated method. [28,30,[50][51][52] In the present study, we have synthesized graphene-CdS nanocomposites with a facile approach at low-temperatures and less reaction time, which is eco-friendly and cost-effective. Further exploration in an extensive literature review indicates that among all the reported literature, our catalyst has served as a better photocatalyst with lower catalyst dosage and less reaction time.…”
Section: Photocatalytic Pathwaymentioning
confidence: 99%
“…so this is the problem it can be overcome by combining them photosensitizer. [27][28][29][30][31] The nanocomposites of CdS such as Fe 3 O 4 /CdS/ZnS, CuO/CdS, CdS/ TiO 2 , and CdS/ZnS/BiPO 4 have received special attention as well in photocatalysis for reaching enhanced photocatalytic activities. [27,[32][33][34] Several studies have reported the photocatalytic removal of CPY present in wastewater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lightness, ease of processing, ideal mechanical robustness, and simplicity of machining made polymers an interesting backbone resource for different industries. [1][2][3] The properties of PCs can also be modified by fibers and nanoparticles, or they can even be blended with other polymers to create a variety of combinations and variants, depending on the application's requirements. An organic and an inorganic component of a biopolymer have the same molecular unit in their molecular framework.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility and unique characteristics of polymers and their polymer composites (PCs) motivated the research community to investigate their potential for different practical applications with pre‐defined functions. The lightness, ease of processing, ideal mechanical robustness, and simplicity of machining made polymers an interesting backbone resource for different industries [1–3] . The properties of PCs can also be modified by fibers and nanoparticles, or they can even be blended with other polymers to create a variety of combinations and variants, depending on the application‘s requirements.…”
Section: Introductionmentioning
confidence: 99%